Architecture and its Occupants: Perceptions of Students and Faculty at Two Programs - Thakur, Anubhuti (Nurture, 2009)
This study aimed to identify the perceptions of students and faculty at two architecture programs in the Southeastern United States about the effects of architecture design decisions on occupants. The data revealed that students and professors acknowledged various human issues in the design projects which were divided in five categories: (1) Interaction with building, (2) Image of the building, (3) Effects on occupant behavior, (4) Feeling within the space, and (5) Other related concerns. These categories are discussed and comparisons drawn to identify the nature of architecture pedagogy with reference to occupants’ experiences in architectural spaces. Suggestions are made for architecture curricula to ensure that the understanding of these concerns among students and faculty is fully harnessed and nurtured.